ENKRIPSI DATABASE SISTEM INFORMASI HELPDESK DENGAN ALGORITME KRIPTOGRAFI AES-128 DAN VIGENERE CHIPER - Ruswandi, Muhammad Apit; Windarto, Windarto (Universitas Budi Luhur, 2022)
Information technology has benefits to help and make it easier for humans to do everything in sharing communication. During the pandemic, PT. Royal Audrey Megah is one of the companies implementing Work From Home (WFH). To maintain a good quality of support in hosting services, the Customer Service and IT Support division can access helpdesk application through the internet connection. Applications that can be accessed from the internet bring many benefits to their users, even though not spared from their negative impacts. Given this, data is a very valuable asset and must be protected. Data security can be done, one of which is by securing from the database side. Database security can be done by implementing symmetric cryptography Advance Encryption Standard (AES) and Vigenere. The purpose of this study is to minimize the occurrence of database leaks and misuse by irresponsible parties. The cryptographic techniques used are the Advanced Encryption Standard (AES) and vigenere methods. From the results of the implementation, it was concluded that the application is able to secure data in an encrypted database so that it can minimize the occurrence of misuse or manipulation of data by people who do not have authority over the data.